Как управлять экономикой - Попов Гавриил Харитонович (Педагогика, 1989)
Экземпляры: ф-13 (реторконверсия) / Инвентарный номер: 27534 / Цена: 0.35 / Сис.шифр: 65.050.9(2) / Авт.знак: П58 / ГРНТИ: 06 / ББК: 65.050.9(2)